Anne Bogart: „Teatrul a devenit pentru mine un refugiu, un sanctuar“ - Ardelean, Ioan; Anne, Bogart (Theatrical Research, 2024)
Anne Bogart: "For me, the theatre has become a refuge, a sanctuary" An interview with Anne Bogart, American director and pedagogue, renowned not only for her musicals, but also for her viewpoints technique, in accordance with which space and time contribute to the rewriting of dramatic scenes. Having authored the seminal work A Director Prepares, Anne Bogart has imbued the dramatic and the artistic with her own form of expression, emphasizing notions such as courage, perseverance and trust.